Infection Control at a Government Hospital in Pakistan - Baqi, Shehla; Damani, Nizam N; Shah, Sharaf Ali; Khanani, Rafiq (International Journal of Infection Control, 2009)
An Infection Control survey of a government hospital in Pakistan was conducted in 2007. The hospital did not have an Infection Control committee or policies. Of 13 inpatient units, only the 2 ICUs had hand hygiene (HH) facilities. Health care workers (HCWs) did not demonstrate hand hygiene during patient care. In the ICUs, gowns were shared amongst HCWs. Sharps were thrown in the garbage pail. Urinary catheter bags were emptied by janitors into patient garbage pails. Isolation precautions were not observed with patients of tuberculosis or multi-drug resistant organisms. The Dental clinic had no autoclave. In the Surgery clinic, over 50 proctoscopies were performed without disinfection. The Isolation Ward did not have HH or appropriate isolation facilities. In a spot survey of 86 HCWs, 85% had sustained needle stick injuries. Correct Infection Control practices are not followed at the hospital. There is an urgent need to establish an Infection Control Programme.